Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbasis Media Ular Tangga Pada Mata Pelajaran Al Qur’an Hadis Kelas XII Di Madrasah Aliyah Negeri 1 Jembrana - Rosidatul Ulya, Syukriana; Widodo , Ari Dwi (Cendekia : Jurnal Pendidikan dan Keagamaan, 2025)
The problem that occurs in the process of implementing Al-Qur'an Hadith learning is the lack of attractive learning methods or models used by teachers so that students do not understand the material taught by the teacher. The aim of this research is to describe the application of the Teams Games Tournament (TGT) Cooperative Learning Model based on Snakes and Ladders Media, Supporting and Inhibiting Factors of the Teams Games Tournament (TGT) Cooperative Learning Model based on Snakes and Ladders Media in the Qur'an Hadith class XII class at Madrasah Aliyah Negeri 1 Jembrana. Data collection techniques are observation, interviews and documentation. Data analysis according to Miles and Huberman, namely collecting data, reducing data, presenting data and drawing conclusions. The validity of the data is triangulation of sources and techniques. The results of this research are: 1. The application of the teams games tournament (TGT) type learning model based on snakes and ladders media is learning in groups of 4-6 people, training cohesiveness, understanding the material, developing thinking skills, a sense of respect and helping each other. There are 3 learning activities, namely: preliminary activities, core activities and closing activities. Assessment includes: pretest, formative assessment and summative assessment. 2. Supporting and inhibiting factors in implementing the teams games tournament (TGT) type learning model based on snakes and ladders media. Supporting factors are the use of appropriate media, adequate facilities and infrastructure, students who are enthusiastic and enthusiastic and comfortable in learning activities. Inhibiting factors are different learning characteristics, students' lack of self-confidence and limited time for learning activities